2017
DOI: 10.21037/acs.2017.05.09
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol septal ablation: in which patients and why?

Abstract: At present, surgical septal myectomy is regarded as the "gold standard" treatment for most patients with obstructive hypertrophic cardiomyopathy (HCM) and drug-refractory symptoms. However, the best results are obtained by those surgeons who have extensive experience with this operation at a small number of referral centers. In the mid-1990s, percutaneous alcohol septal ablation was introduced as an alternative to myectomy to reduce LV outflow gradient and heart failure symptoms in patients with obstructive HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…For HCM with subaortic obstruction and severe drug-refractory symptoms, surgical septal myectomy should be the gold standard for septal reduction therapy in centers with comprehensive experience (15). Alcohol septal ablation (ASA) has been proposed as a less invasive alternative to surgical myectomy in patients with advanced age, those that had previously received a pacemaker or defibrillator, as well as those with significant comorbidities and a strong aversion to surgery (16,17). Seggewiss and Faber (18) have reported on a case of mid-ventricular obstruction, which responded favorably to alcohol ablation.…”
Section: Discussionmentioning
confidence: 99%
“…For HCM with subaortic obstruction and severe drug-refractory symptoms, surgical septal myectomy should be the gold standard for septal reduction therapy in centers with comprehensive experience (15). Alcohol septal ablation (ASA) has been proposed as a less invasive alternative to surgical myectomy in patients with advanced age, those that had previously received a pacemaker or defibrillator, as well as those with significant comorbidities and a strong aversion to surgery (16,17). Seggewiss and Faber (18) have reported on a case of mid-ventricular obstruction, which responded favorably to alcohol ablation.…”
Section: Discussionmentioning
confidence: 99%
“…The effects are limited by anatomical morphology, perforator artery distribution, and collateralization. 14 22 Turina et al 23 first reported development of CHF associated with left ventricular dilatation at 8 years after surgical septal myectomy. In fact, previous studies found global strain in patients with HCM was significant reduced compared with healthy subjects despite normal left ventricular function as assessed by standard criteria such as LVEF or fraction shortening, suggesting the presence of a global subclinical systolic dysfunction.…”
Section: Predictors Of the Composite Endpointmentioning
confidence: 99%
“…Thus, worldwide practiced ASA procedures have unexpectedly and paradoxically increased the number of septal myectomy to some extent. 14 Nevertheless, surgical treatment for this subgroup of patients can be very tough and challenging, and regarding studies are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…LVOT pressure gradients are most often measured noninvasively by Doppler, but in some patients with eccentric mitral regurgitation accurate measurement is challenging and invasive measurement may be required. Invasive LVOT gradients are also evaluated during alcohol septal ablation procedures . Invasive exercise LVOT gradient measurement is impractical for most catheterization laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive LVOT gradients are also evaluated during alcohol septal ablation procedures. 9,10 Invasive exercise LVOT gradient measurement is impractical for most catheterization laboratories. Invasive provocation methods include Valsalva maneuvers, isoproterenol infusion, and the postpremature ventricular contraction (PVC) responses to induced or spontaneous ventricular ectopy.…”
Section: Introductionmentioning
confidence: 99%